2017
DOI: 10.1007/s00520-017-3746-0
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and impact of severe fatigue in adolescent and young adult cancer patients in comparison with population-based controls

Abstract: PurposeThe current study determined the prevalence of severe fatigue in adolescent and young adult (AYA) cancer patients (aged 18–35 years at diagnosis) consulting a multidisciplinary AYA team in comparison with gender- and age-matched population-based controls. In addition, impact of severe fatigue on quality of life and correlates of fatigue severity were examined.MethodsAYAs with cancer (n = 83) completed questionnaires including the Checklist Individual Strength (CIS-fatigue), Quality of Life (QoL)-Cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 31 publications
4
40
0
Order By: Relevance
“…Poort et al examined the association between FCR and fatigue severity by the Cancer Worry Scale and Checklist Individual Strength (CIS‐fatigue). Findings revealed that higher FCR was moderately correlated with fatigue severity .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Poort et al examined the association between FCR and fatigue severity by the Cancer Worry Scale and Checklist Individual Strength (CIS‐fatigue). Findings revealed that higher FCR was moderately correlated with fatigue severity .…”
Section: Resultsmentioning
confidence: 99%
“…Poort et al examined the association between FCR and fatigue severity by the Cancer Worry Scale and Checklist Individual Strength (CIS‐fatigue). Findings revealed that higher FCR was moderately correlated with fatigue severity . Studies also found that FCR may lead to decreased breast self‐examination frequency and less nicotine dependence .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their cancer diagnoses and treatments significantly disrupt their developmental trajectories and construction of personal identity in crucial areas such as education, career, and social relationships. [2][3][4][5] After treatment, they face multifaceted survivorship issues including fatigue, 6,7 psychosocial problems, 8 and practical financial concerns [9][10][11] that can greatly impede their transition back to work or school. 12 A growing body of literature has elucidated AYA cancer survivors' diverse needs.…”
Section: Introductionmentioning
confidence: 99%